Good practices in sustainability reporting: Evidence from the Romanian banking sector - Claudia Gabriela Baicu; Simona Poladian; Alina-Cerasela Aluculesei; Sorin-Nicolae Curcă (Amfiteatru Economic, 2025)
This article investigates good practices in sustainability reporting in the Romanian banking sector. Since such a complex endeavour has not been carried out in the financial field in Romania, and the data regarding national reporting is lacking, the methodological approach combines qualitative analysis of secondary data with the results of a survey based on a questionnaire. The documents were investigated using the content analysis method based on predefined keywords and focused on the sustainability reports published by the most important banks and the documents they disseminated in the public space. The obtained results were supplemented by those based on the questionnaire distributed among six managers from the country's banking institutions and interpreted based on thematic analysis. The research findings show that less than half of the banks in Romania, which account for about 80% of the net assets of credit institutions, publish annual sustainability reports following international reporting standards. The information disclosed includes good practices related to carbon footprint mitigation measures, sustainability governance, environmental risk management, and green finance. The results of the investigation reveal that, although green loans have a number of advantages, green finance in Romania faces obstacles, including those related to the additional reporting costs. The article contributes to a better understanding and awareness of the real limitations in sustainability reporting and supports the development of coherent measures to assist banking institutions in improving the way they communicate information to the public.
Keywords: G21; G38; F64; Q56; 330; sustainability reporting; sustainability; good reporting practices; green finance; Romanian banking sector